DETERMINAN KEMISKINAN PAD A6 PROVINSI DI PULAU JAWA TAHUN 2012-2021 - refani camelia; Ashar, Khusnul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Poverty is a global problem that is a widespread phenomenon that occurs in many countries. Poverty is one of the factors to see the welfare of the people in a region. The poverty condition of a country is a reflection of the welfare level of the country's population. The purpose of this study is to determine the determinants of poverty in 6 provinces in Java Island in 2012-2021. Java Island was chosen because among other islands, Java Island is a more productive island but one of its provinces has a percentage rate of poor people of more than 10% in 10 years. The influential factors in this study that affect poverty include the level of investment, education with the average years of schooling indicator, and the provincial minimum wage. The type of data used is panel data with a cross-section of 6 provinces from 2012-2021. The research method used is panel data regression analysis. The regression results show that the education variables have no effect on poverty, while the investment and minimum wage variable has an effect on poverty. For the F test, it can be seen that the three independent variables jointly affect the dependent variable.